2018
DOI: 10.1186/s40101-018-0177-7
|View full text |Cite
|
Sign up to set email alerts
|

Energy cost and lower leg muscle activities during erect bipedal locomotion under hyperoxia

Abstract: BackgroundEnergy cost of transport per unit distance (CoT) against speed shows U-shaped fashion in walking and linear fashion in running, indicating that there exists a specific walking speed minimizing the CoT, being defined as economical speed (ES). Another specific gait speed is the intersection speed between both fashions, being called energetically optimal transition speed (EOTS). We measured the ES, EOTS, and muscle activities during walking and running at the EOTS under hyperoxia (40% fraction of inspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 52 publications
(95 reference statements)
3
9
0
Order By: Relevance
“…These results were equivalent to those of our recent studies that measured TA activity during walking and running at the EOTS (Abe, Fukuoka & Horiuchi, 2017;Abe et al, 2018), which suggested that the motor unit recruitment pattern of the TA shifted more toward Type I (slow twitch) fibers rather than Type II (fast twitch) fibers after the walk-run transition. Several studies have also reported that an abrupt increase in TA activity associated with the walk-run transition (Hreljac, 1995;Hreljac et al, 2008;Bartlett & Kram, 2008;Malcolm et al, 2009;Shih et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These results were equivalent to those of our recent studies that measured TA activity during walking and running at the EOTS (Abe, Fukuoka & Horiuchi, 2017;Abe et al, 2018), which suggested that the motor unit recruitment pattern of the TA shifted more toward Type I (slow twitch) fibers rather than Type II (fast twitch) fibers after the walk-run transition. Several studies have also reported that an abrupt increase in TA activity associated with the walk-run transition (Hreljac, 1995;Hreljac et al, 2008;Bartlett & Kram, 2008;Malcolm et al, 2009;Shih et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…An abrupt increase in muscle activity of the dorsiflexor (tibialis anterior; TA) has been observed when participants walked at a speed close to the PTS (Hreljac, 1995;Hreljac et al, 2008;Prilutsky & Gregor, 2001; Bartlett & Kram, 2008;Malcolm et al, 2009;Shih et al, 2016), and our recent studies showed muscle activity of the TA decreased when participants switched from walking to running at the EOTS (Abe, Fukuoka & Horiuchi, 2017;Abe et al, 2018). In association with a decrease in TA activity when switching the gait pattern, mean power frequency (MPF; Hz) of the TA became lower, suggesting that more Type 1 muscle fibers were recruited in the TA during running than walking at the EOTS.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…An abrupt increase in muscle activity of the dorsiflexor ( tibialis anterior ; TA) has been observed when participants walked at a speed close to the PTS (Hreljac, 1995; Hreljac et al, 2008; Prilutsky & Gregor, 2001; Bartlett & Kram, 2008; Malcolm et al, 2009; Shih et al, 2016), and our recent studies showed muscle activity of the TA decreased when participants switched from walking to running at the EOTS (Abe, Fukuoka & Horiuchi, 2017; Abe et al, 2018). In association with a decrease in TA activity when switching the gait pattern, mean power frequency (MPF; Hz) of the TA became lower, suggesting that more Type I muscle fibers were recruited in the TA during running than walking at the EOTS.…”
Section: Introductionmentioning
confidence: 82%
“…An alteration of the MPF values between walking and running allows us to evaluate muscle fiber recruitment pattern in each gait. The sum of the rectified EMG (µV·s) was normalized by measured time (s) and number of steps to cancel the effects of step frequency (Abe, Fukuoka & Horiuchi, 2017; Abe et al, 2018). The EMG values obtained were further normalized to those obtained at 1.11 m·s −1 under each condition.…”
Section: Methodsmentioning
confidence: 99%